Media Literacy in the Family (Descriptive Study of parents' Actions of SDIT ALFAUZIEN Depok Students in Assisting the Use of Media in Children) - Chendi Liana; Herta A Soemardjo (Universitas Pendidikan Nasional, 2022)
This study aims to determine the benefits of media literacy in families where parents carry out acts of assisting the use of media in children. The research used qualitative and descriptive methods with in-depth interviews and observations of parents when mentoring the children of SDIT ALFAUZEIN while watching television programs. This study shows that parents are not optimal in providing assistance to children when watching television because of busyness. This adversely affects the psychology and behavior of children because they have not been able to distinguish between actual or manipulative impressions. To carry out media literacy in the family, parents should spend time mentoring, communicating, and being critical of the impressions consumed by children. Limiting time, providing means of activity, and interesting recreation so that children do not spend their time-consuming television shows. Literacy assistance in the family is beneficial for the mental development of children. And, the government prepares regulations for television shows and publishes television manuals so that people become critical and literate in media literacy.